Extending NMR Quantum Computation Systems by Employing Compounds with Several Heavy Metals as Qubits - Jéssica Boreli dos Reis Lino; Mateus Aquino Gonçalves; Stephan P. A. Sauer; Teodorico Castro Ramalho (Magnetochemistry, 2022)
Nuclear magnetic resonance (NMR) is a spectroscopic method that can be applied to several areas. Currently, this technique is also being used as an experimental quantum simulator, where nuclear spins are employed as quantum bits or qubits. The present work is devoted to studying heavy metal complexes as possible candidates to act as qubit molecules. Nuclei such 113Cd, 199Hg, 125Te, and 77Se assembled with the most common employed nuclei in NMR-QIP implementations (1H, 13C, 19F, 29Si, and 31P) could potentially be used in heteronuclear systems for NMR-QIP implementations. Hence, aiming to contribute to the development of future scalable heteronuclear spin systems, we specially designed four complexes, based on the auspicious qubit systems proposed in our previous work, which will be explored by quantum chemical calculations of their NMR parameters and proposed as suitable qubit molecules. Chemical shifts and spin–spin coupling constants in four complexes were examined using the spin–orbit zeroth-order regular approximation (ZORA) at the density functional theory (DFT) level, as well as the relaxation parameters (<semantics>T1</semantics> and <semantics>T2</semantics>). Examining the required spectral properties of NMR-QIP, all the designed complexes were found to be promising candidates for qubit molecules.